2021
DOI: 10.1158/1940-6207.capr-21-0063
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Vaccine HPV Type Infections in a Young Women Group (18–25 Years) Five Years after HPV Vaccine Introduction in Colombia

Abstract: Background/Objectives.In Colombia, the HPV vaccine was launched in 2012 in the context of a school-based national vaccination program targeting girls aged 9-14 and offering catch up vaccination for girls aged 14-17. In this study, we evaluated the program's impact on type-specific HPV infection by comparing HPV cervical prevalence among vaccinated and non-vaccinated women.Methods. This is a comparative cross-sectional study conducted 5 years after the quadrivalent HPV vaccination implementation in a sentinel C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…In the communities of the Paujil Reserve, genotype 16 was the number one genotype, followed by 52 , 66 and 68 , all in second place. Angarita & Forero [ 9 ] found genotype 16 to be the number one followed by genotypes 31 and 39 ; Cómbita et al [ 26 ] also described genotype 16 as number one, followed by 52 , 58 and 51 in an unvaccinated population of the city of Bogota. Puerto et al [ 10 ] reported genotype 16 as number one, followed by 52 and 51 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the communities of the Paujil Reserve, genotype 16 was the number one genotype, followed by 52 , 66 and 68 , all in second place. Angarita & Forero [ 9 ] found genotype 16 to be the number one followed by genotypes 31 and 39 ; Cómbita et al [ 26 ] also described genotype 16 as number one, followed by 52 , 58 and 51 in an unvaccinated population of the city of Bogota. Puerto et al [ 10 ] reported genotype 16 as number one, followed by 52 and 51 .…”
Section: Discussionmentioning
confidence: 99%
“…HPV-DNA was screened for 19 HR and 9 LR genotypes through the use of the Anyplex II 1 Real Time Polymerase Chain Reaction (TR-PCR) HPV 28 by SEEGENE 1 detection technique. The high oncogenic risk viral genotypes (HR-HPV) were: 16,18,26,31,33,35,39,45,51,52,53,56,58,59,66,68,69,73,82. The LR-HPV genotypes were : 6, 11, 40, 42, 43, 44, 54, 61 and 70.…”
Section: Clinical Specimen Collectionmentioning
confidence: 99%
“…21 They also emphasize that the monitoring of HPV vaccines post licensure plays an important role in assessing the progress of immunization programs, demonstrating the impact of vaccines on the population, and providing data for policy needs. 22,23 A study in northern Zimbabwe suggested that determining whether cross-immunization against genotypes causing invasive cervical cancer develops after administration of the vaccines in current use is very important. 24 A limitation of the study is that as the proportion of women who came forward for screening was less than half, prevalence has been calculated based on women who were screened.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in Columbia and Brazil show that HPV types 16, 18, 31, 33, 35, 45, 52, and 58 should be given priority when the protective effects of current vaccines are assessed 21 . They also emphasize that the monitoring of HPV vaccines post licensure plays an important role in assessing the progress of immunization programs, demonstrating the impact of vaccines on the population, and providing data for policy needs 22,23 . A study in northern Zimbabwe suggested that determining whether cross‐immunization against genotypes causing invasive cervical cancer develops after administration of the vaccines in current use is very important 24 …”
Section: Discussionmentioning
confidence: 99%